Perencanaan Strategi Pemasaran Pondok Pesantren Darul Ilmi Wal Amal - Nurlenawati, Netti; Sumarni, Neni; Tuhagana, Aji; Lubis, Haya Maharani (Universitas Batanghari, 2024)
The purpose of this research is to determine the strategic positioning and alternative marketing strategy that can be carried out by Darul Ilmi wal Amal Islamic Boarding School. The method used in this research is a descriptive method with a qualitative approach. The data analysis used is SWOT analysis (Strength, Weakness, Opportunity, Threat) which is measured through internal factors (Internal Strategic Factor Analysis Summary/IFAS) and external factors (External Strategic Factor Analysis Summary/EFAS). The results obtained from IFAS and EFAS show that Darul Ilmi wal Amal Islamic Boarding School is in quadrant I, which is a position that shows a strong organization with great opportunities. The strategy that is in accordance with this position is a development strategy (progressive/aggressive/expansion) which includes preparation towards a muadalah-based boarding school; expansion of promotion by involving various related parties and using various effective methods; expansion of cooperation with various related parties, especially in admitting new students, education and training; determining affordable prices/fees, scholarship programs for students and organizing the learning process based on the different academic abilities of students in the form of study groups.